Arginase‐1 is neither constitutively expressed in nor required for myeloid‐derived suppressor cell‐mediated inhibition of T‐cell proliferation. Issue 6 (23rd March 2018) - Bian, Zhen; Abdelaal, Ahmed Mansour; Shi, Lei; Liang, Hongwei; Xiong, Lanqiao; Kidder, Koby; Venkataramani, Mahathi; Culpepper, Courtney; Zen, Ke; Liu, Yuan
Abstract: Although previous reports suggest that tumor‐induced myeloid‐derived suppressor cells (MDSC) inhibit T cells by L‐arginine depletion through arginase‐1 activity, we herein show that arginase‐1 is neither inherently expressed in MDSC nor required for MDSC‐mediated inhibition. Employing Percoll density gradients, large expansions of MDSC in the bone marrow of tumor‐bearing mice were isolated and demonstrated potent inhibition in T‐cell proliferation activated by TCR‐ligation, Concanavalin A, PMA plus ionomycin, or IL‐2. Despite demonstrating characteristic immunosuppressive capacity, these MDSC exhibit no arginase‐1 expression and/or exert their inhibitory effects independent of arginase‐1 activity. However, arginase‐1 expression in MDSC can be induced by exposure to TCR‐activated T cells or their culture medium, but not T cells activated by other means or growing tumor cells. Further investigation reveals multiple cytokines secreted by TCR‐activated T cells as orchestrating two signaling‐relay axes, IL‐6‐to‐IL‐4 and GM‐CSF/IL‐4‐to‐IL‐10, leading to arginase‐1 expression in MDSC. Specifically, IL‐6 signaling increases IL‐4R, enabling IL‐4 to induce arginase‐1 expression; similarly, GM‐CSF in concert with IL‐4 induces IL‐10R, allowing IL‐10‐mediated induction. Surprisingly, our study indicates that induction of arginase‐1 expression is not conducive to the critical MDSC‐mediated inhibition toward T cells, which is rather dependent on direct cell contacts undiminished by PD‐L1 blockade or SIRPα deficiency. Abstract : Arginase‐1 expression in MDSCs can be induced by exposure to TCR‐activated T cells but not T cells activated by ConA, PMA or IL‐2. IL‐6‐to‐IL‐4 and GM‐CSF/IL‐4‐to‐IL‐10 signaling axes lead to arginase‐1 expression in MDSCs. However, MDSC‐mediated inhibition toward T cells is independent of arginase‐1 but requires direct cell contact.